2005
DOI: 10.1016/j.micinf.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to individual proteins of SARS coronavirus and their neutralization activities

Abstract: A novel coronavirus, the severe acute respiratory syndrome (SARS) coronavirus (SARS-CoV), was identified as the causative agent of SARS. The profile of specific antibodies to individual proteins of the virus is critical to the development of vaccine and diagnostic tools. In this study, 13 recombinant proteins associated with four structural proteins (S, E, M and N) and five putative uncharacterized proteins (3a, 3b, 6, 7a and 9b) of the SARS-CoV were prepared and used for screening and monitoring their specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
131
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 28 publications
6
131
0
4
Order By: Relevance
“…The immunogenic properties of ORF3a in SARS-CoV-infected patients has been shown to vary depending on: (i) whether or not the sera was collected from convalescent or recovered patients; (ii) whether or not full-length or truncated fusion proteins were used to detect immunoglobulin G (IgGs) to ORF3a; and (iii) the method used to detect these antibodies to ORF3a, namely western blot, ELISA or protein microarrays. To date, in general, IgGs to ORF3a could be detected in only ~60–73% of patient sera screened [35,57,58,59]. This could be due to frame-shift mutations within the 3a gene, resulting in a heterogeneous population of sgRNA3 transcripts in patients with acute SARS-CoV infection containing copies of both wild-type and mutant 3a genes.…”
Section: Sars Accessory Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…The immunogenic properties of ORF3a in SARS-CoV-infected patients has been shown to vary depending on: (i) whether or not the sera was collected from convalescent or recovered patients; (ii) whether or not full-length or truncated fusion proteins were used to detect immunoglobulin G (IgGs) to ORF3a; and (iii) the method used to detect these antibodies to ORF3a, namely western blot, ELISA or protein microarrays. To date, in general, IgGs to ORF3a could be detected in only ~60–73% of patient sera screened [35,57,58,59]. This could be due to frame-shift mutations within the 3a gene, resulting in a heterogeneous population of sgRNA3 transcripts in patients with acute SARS-CoV infection containing copies of both wild-type and mutant 3a genes.…”
Section: Sars Accessory Proteinsmentioning
confidence: 99%
“…The sera from rabbits immunized with recombinant ORF3a (a.a. 125–274) does not exhibit any significant neutralizing activity on SARS-CoV infected Vero E6 cells [59]. In another study, however, sera from rabbits immunized with a different recombinant ORF3a (a.a. 15–28) contains neutralizing antibodies that do inhibit SARS-CoV infection in Vero E6 cells [61].…”
Section: Sars Accessory Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where necessary, the presence of neutralizing antibodies could be subsequently confirmed for strong-responder samples by HAI or MN. Proteome profiling via protein microarrays has proven useful in many studies focused on understanding basic biochemical processes [xviii, xix, xx], but, more germane to the research reported herein, microarrays have also been used to discover antigenic proteins and monitor immunological responses to them [xxi, xxii, xxiii]. Thus, antigen arrays would seem to be ideal for the development of influenza surveillance and immunity screening tools.…”
mentioning
confidence: 99%